P825 Low-prevalence of NOD2 polymorphisms in a Maltese IBD cohort. (25th January 2019) - Schembri, J; Pace, N; Degenhardt, F; Franke, A; Ellul, P
Abstract: Background: NOD2 was the first IBD susceptibility gene to be discovered, back in 2001. Despite the discovery of many other susceptibility loci, NOD2 remains of interest as it is one of the few risk loci that is not shared between Ulcerative colitis (UC) and Crohn's disease (CD), as it only contributes to the latter. Whilst NOD2 polymorphisms are very common in European CD patients, prior study on 83 Maltese CD patients showed low prevalence of the 3 main NOD2 polymorphisms: p.Arg702Trp, p.Gly908Arg and p.Leu1007fsinsC. Methods: We conducted a case–control discovery genetic association study using the Illumina Immunochip (v2) as a genotyping platform. 517 individuals were recruited, however, after strict quality control (QC), 160 CD, 93 UC and 188 healthy controls (HC) remained. Results: Gender distribution was approximately equal between all groups. Table 1 is a summary of baseline characteristics and demographic data of our study cohort. Baseline characteristics of case and control subjects. Principal component plot showing clustering of Maltese individuals (crosses) close to other European populations. This was the first genome-wide association study ever conducted in a Maltese population. Principal component analysis shows clustering of Maltese individuals (crosses) close to other European ethnicities from the 1000 genomes project, the TSI (Toscani from Italy) group being closest. Table 1 summarises minor allele frequencies (MAF) for the 3 common NOD2 polymorphisms in our population. Conclusions: Prevalence of NOD2 polymorphisms was similar between CD, UC and HC individuals hence it is unlikely for this gene to be contributing significantly towards IBD susceptibility in our population. Despite the relatively small sample size, we have validated findings from prior research that have used low-throughput genotyping techniques. Furthermore, the studied population represents approximately one fourth of the entire current Maltese IBD population. Whilst low prevalence of NOD2 polymorphisms has been documented in other populations. 1 To the best our knowledge this is the first such finding in a population demonstrating European ancestry. Reference 1. Liu JZ et al . Association analyses identify 38 susceptibility loci for inflammatory bowel disease and highlight shared genetic risk across populations. Nat Genet 2015;47:979–986.